Modelling foundations and applications : 12th European Conference, ECMFA 2016, held as part of STAF 2016, Vienna, Austria, July 6-7, 2016, Proceedings /: 12th European Conference, ECMFA 2016, held as part of STAF 2016, Vienna, Austria, July 6-7, 2016, Proceedings. (2016) - Unknown
No abstract available